Transformation of Lagerstroemia indica by improved Agrobacterium-mediated floral-dip and pollen-tube pathway method - CHEN Yan; SUN Kuan-ying; ZHANG Tao (浙江大学学报. 农业与生命科学版)
Lagerstroemia indica was transformed by an improved Agrobacterium-mediated floral-dip and pollen-tube pathway method, respectively, using green fluorescent protein gene (GFP) as a report gene, and its fruit number, rate of seed-setting set and seedling rate were counted. The transformed plants were screened from the 28-day seedlings irradiated by a portable ultraviolet lamp at 365 nm. The experimental results showed that the rate of seed-setting set and seedling rate by pollen-tube pathway method were significantly higher than those by the floral-dip method. The transformation rate of L. indica by the floral-dip method was higher by 0.06% than that by the pollen-tube pathway, which didn't yet reach significant levels. The rate of seed-setting set by the pollen-tube pathway method was higher by 11.87% -26.74% than that by the floral-dip method, indicating that the pollen-tube pathway method is more beneficial for transformation of L. indica.